Analysis of the Status of Chinese clinical practice guidelines development - Zheng Zhi-hong; Cui Shu-qi; Lu Xiao-qin; Zakus David; Liang Wan-nian; Huang Fang; Cao Xiao-na; Zhao Ya-li; Peng Xiao-xia; Rao Ke-qin; Wu Jing (BMC, 2012)
Abstract Background The work of developing clinical practice guidelines began just a little more than ten years ago in China. Up to now, there have been few studies about them. Objectives To review and analyze the status of Chinese clinical practice guidelines in 1997-2007. Methods All Chinese guidelines from 1997-2007 were collected, and made a regression analysis, and a citation analysis for evaluating the impact of guidelines. To analyze the developing quality, the most influential guidelines were evaluated with AGREE instrument, and each guideline was evaluated to check for any updating. In order to analyze the objective and target population, all guidelines were classified and counted separately according to disease/symptom center, and whether towards specialists or general practitioners. Results 143 guidelines were collected. An exponential function equation was established for the trend in the number of guidelines. The immediacy index in every year was very low while the average citation rate was not. Both the percentages of highly cited and never cited were high. For the evaluation with AGREE, only the average score of clarity and presentation was high (89.9%); the remaining were much lower. Editorial independence scored 0. Only 27 (18.9%) of 143 guidelines, were found to be evidence-based. Only a few had ever been updated, with an average updating interval of 5.2 years. Only 2.1% were symptom-centered, and only 4.2% were aimed at general practitioners. Conclusion Much progress has been obtained for Chinese guidelines development. However, there were still defects, and greater efforts should be made in the future.